Association of ANRIL polymorphisms with coronary artery disease: A systemic meta-analysis. Issue 42 (16th October 2020) - Zhang, Ya-nan; Qiang, Bo; Fu, Li-juan
Abstract: Background: The long noncoding RNAs have gradually been reported to be an important class of RNAs with pivotal roles in the development and progression of myocardial infarction (MI). In this study, we hypothesized that genetic variant of cyclin-dependent kinase inhibitor 2B antisense RNA (ANRIL) may affect the prognosis of MI patients. Methods: A systematic review and meta-analysis of studies including 11, 269 cases and 10, 707 controls on the association of 5 ANRIL single nucleotide polymorphism and the overall risk of MI or coronary artery disease (CAD) was performed. Results: In the meta-analysis, rs4977574 A > G, rs1333040 C > T, rs1333042 A > G and rs10757274 A > G ANRIL polymorphisms were correlated with overall MI or CAD risk. No significant associations were found between ANRIL rs1333049 G > C polymorphism and CAD risk. Conclusions: The results indicated that ANRIL polymorphism (rs4977574, rs1333040, rs1333042, and rs10757274) were more generally associated with CAD or MI risk. Further experimental studies to evaluate the limits of this hypothesis are warranted, and future functional studies are required to clarify the possible mechanisms. Abstract : Supplemental Digital Content is available in the text